Efficient lung cancer-targeted drug delivery via a nanoparticle/MSC system - Xusheng Wang; Haiyan Chen; Xiaowei Zeng; Wenpeng Guo; Yu Jin; Shan Wang; Ruiyun Tian; Yanjiang Han; Ling Guo; Jimin Han; Yaojiong Wu; Lin Mei (Elsevier, 2019)
Low targeting efficiency limits the applications of nanoparticles in cancer therapy. The fact that mesenchymal stem cells (MSC) trapped in the lung after systemic infusion is a disadvantage for cell therapy purposes. Here, we utilized MSC as lung cancer-targeted drug delivery vehicles by loading nanoparticles (NP) with anti-cancer drug. MSC showed a higher drug intake capacity than fibroblasts. In addition, MSC showed predominant lung trapping in both rabbit and monkey. IR-780 dye, a fluorescent probe used to represent docetaxel (DTX) in NP, delivered via MSC accumulated in the lung. Both in vitro MSC/A549 cell experiments and in vivo MSC/lung cancer experiments validated the intercellular transportation of NP between MSC and cancer cells. In vivo assays showed that the MSC/NP/DTX drug delivery system exerted primary tumor inhibition efficiency similar to that of a NP/DTX drug system. Collectively, the MSC/NP drug delivery system is promising for lung-targeted drug delivery for the treatment of lung cancer and other lung-related diseases. KEY WORDS: Mesenchymal stem cells, Nanoparticle, Drug delivery, KrasG12D, Lung cancer